Expression of EGFR, HER2, phosphorylated ERK and phosphorylated MEK in colonic neoplasms of familial adenomatous polyposis patients. - Wang, J; Hollingshead, J; El-Masry, N; Horncastle, D; Talbot, I; Tomlinson, I; Alison, MR; El-Bahrawy, M (2012)
PURPOSE: The expression of epidermal growth factor receptor (EGFR) and human epidermal growth factor receptor 2 (HER2) is associated with poor prognosis in sporadic colorectal carcinoma (CRC). EGFR inhibitors are approved for the treatment of refractory CRC. The aim of this study was to investigate the expression of EGFR and HER2 and downstream extracellular signal regulated kinase (ERK) and mitogen activated protein kinase (MAPK) in non-neoplastic colonic mucosa, adenomas and carcinomas from familial adenomatous polyposis coli (FAP) patients, exploring the expression along the adenoma-carcinoma sequence. METHODS: The expression of EGFR, HER2, phosphorylated MAPK/ERK kinase (pMEK) and phosphorylated ERK (pERK) proteins was studied by immunohistochemistry in samples of colonic non-neoplastic mucosa (n = 65), adenomas (n = 149) and adenocarcinomas (n = 16) from each of the 16 FAP patients. RESULTS: For HER2, only weak cytoplasmic expression was seen in 8% of adenomas, 6% of carcinomas and 3% of the non-neoplastic mucosa. EGFR was expressed in non-neoplastic mucosa, adenomas and carcinomas with a statistically significant increase in expression in adenomas compared with non-neoplastic mucosa (p < 0.001). There was also a statistically significant increase in nuclear staining intensity for pERK (p < 0.001) and pMEK (p < 0.001) in adenomas compared to non-neoplastic mucosa. CONCLUSIONS: This is the first study investigating the expression of these receptors in non-neoplastic mucosa, adenomas and carcinomas from FAP patients. HER2 is not upregulated in the tumours of FAP patients, while EGFR appears to be upregulated in most adenomas and carcinomas, with associated upregulation of pERK and pMEK. We conclude that EGFR and downstream members of its signalling pathway, but not HER2, may be potential therapeutic targets in FAP patients.